THE EFFECTIVENESS OF THE BHINNEKA TUNGGAL IKA COCURRICULAR MODULE BASED ON DEEP LEARNING TO IMPROVE STUDENTS’ NATIONALISM - Ferry Sulistiyono; Triyanto; Endrise Septina Rawanoko (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Globalization will impact the mindset and character of students so that it is required to strengthen nationalism that internalizes the values ​​of Bhinneka Tunggal Ika in co-curricular learning. This study aims to measure the effectiveness of the Bhinneka Tunggal Ika co-curricular module based on deep learning to improve the nationalism of elementary school students. The approach used in this study is a quantitative study with a one-group pretest-posttest design with 25 students as research subjects. The instrument used in this study is a nationalism questionnaire that has been tested for validity and reliability. The data obtained were analyzed descriptively and using the N-gain formula to determine the effectiveness of the use of the Bhinneka Tunggal Ika co-curricular module based on deep learning. The results showed that the average pretest score was 59.36 in the medium category and increased by 21.21 to 80.48 in the posttest and was in the high category. The N-gain calculation showed a value of 0.52 which was in the medium category. This N-gain value indicates that the deep learning-based Bhinneka Tunggal Ika co-curricular module is effective in enhancing students' nationalism. Deep learning can encourage students to understand and internalize the values ​​of Bhinneka Tunggal Ika more deeply and meaningfully. Therefore, the deep learning-based Bhinneka Tunggal Ika co-curricular module can be used as an alternative strategy in strengthening character education in elementary schools, particularly in fostering sustainable student nationalism.